“Minhas Vianas” : a cidade como lugar dos afetos - Santos, Gustavo Pimenta dos (2019)
The city, when thought from its plurality being mediated and understood by the relationships that are built with its dwelling, allow different ways of exploring it to be opportunized due to the varied forms of city living that are produced through experimentation in its open and multiple space. Authors such as Massey (2008), Canevacci (2004), Caiafa (2003; 2005), Marandola Jr. (2011; 2014), Simmel (1973), Maia (2001) and Queiroz (2010; 2015) point us that seeking to understand the urban dwelling as the maximum power of the constitution of the cities' living space it is important to verify the different ways of perceiving the affective flows of sociability and coexistence with indifference that are created from their heterogeneous, polyphonic space, endowed with multiplicity and incessantly crossed by stimuli and provocations. Thus, investigate which relationships are built in the city of Viana Centro that allow it to be understood as the city of affections through the practices and affective flows of sociability and coexistence with indifference, crossed by the experience that permeate their itineraries and living spaces, is the purpose of this work. This area was chosen because it is where I live and also inspires me to want to take on this new analytical stance for understanding the city. Thus, guided by authors such as Jacques (2008), Larrosa (2002), Rolnik (2006) and Becheler (2014), I created a field notebook to investigate and experience the field, using a methodology of analysis based on the theory of drift, psychogeography and construction of situations inspired by the situationist techniques that understand the space as a field to be deciphered from the experience, searching through the drifting releases elements that emerged randomly from this new posture assumed to perceive the Viana City Center, having field reports, affective polyphonic maps and sensitive epilogues. The third and last movement was intended to discuss the methodology used with the obtained data, in order to make discussions about the constructions of the products generated by the field, making analyzes of the perceptions of the flows that each one can promote from the experience in the place and a correlation between them all.